Pengaruh Penambahan Sari Jahe Merah (Zingiber officinale var rubrum) Terhadap Karakteristik Gula Aren Cair (Arenga pinnata Merr.) - Reca Ellisya Virdayanti; Eko Basuki; Dewa Nyoman Adi Paramartha (Jurnal Teknologi dan Mutu Pangan, 2023)
Liquid palm sugar is processed palm sugar in liquid form that contained glucose, maltose and glucose polymer which have deficiencies in nutritional value and benefits for the body. The addition of red ginger extract can increase the benefits of liquid palm sugar. The objective of this study was to determine addition effect of various concentrations of red ginger extract on physical, chemical and sensory quality of liquid palm sugar. The method used in this research was an experimental method with a single factor Completely Randomized Design (CRD), namely concentration 0%; 5%; 10%; 15%; 20% and 25% of red ginger extract. The parameters observed were the acidity (pH), viscosity, total dissolved solids (TDS), moisture content, ash content, antioxidant activity, and sensory properties including color, aroma, taste, and viscosity. Observation data were analyzed by analysis of variance with a significance level of 5%.. The real difference data was further analysis using the Honestly Significant Difference (HSD) test for physical, chemical and sensory parameters. The result showed that the concentration of red ginger extract had a significantly different effect on acidity (pH), viscosity, total dissolved solids (TDS), ash content, moisture content, antioxidant activity, and sensory properties including color (hedonic), aroma (hedonic and scoring), taste (scoring) and texture (hedonic and scoring). The use of 25% red ginger extract was the best treatment to liquid palm sugar with a pH value of 5.61; viscosity 88; TDS 59,8%; Ash Content 0.89%; moisture content 15,03%; Antioxidant Activity 82,83%; and other acceptable sensory qualities.